PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI APARATUR SIPIL NEGARA UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG - Nurkholis, Kgs Muhammad; Berlian, Zainal; Listiawati, Listiawati (Islamic Economics Program, Faculty of Islamic Economics and Business, 2018)
ABSTRACT Purpose of the research are: 1) To Know wheather Leadership Style has any effect on State Civilians Official’s performance of The Islamic State University of Raden Fatah Palembang Regency or not; 2) To Know wheather a Motivation has any effect on State Civilians Official’s performance of The Islamic State University of Raden Fatah Palembang Regency or not; 3) To Know wheather a Work Discipline has any effect on State Civilians Official’s performance of The Islamic State University of Raden Fatah Palembang Regency or not; 3) To Know wheather Leadership Style, Motivation and Work Discipline simultaneously have any effect on State Civilians Official’s performance of The Islamic State University of Raden Fatah Palembang Regency. Population of the research is State Civilians Officials performance of The Islamic State University of Raden Fatah Palembang that’s amount of 152 Officials. Sample of the research is taken 110 officials as respondents. Data analysis instrument is Multiple Linear Regressiuon t-test, F-test and Determination Coefficient Analysis. Conclusions: 1) Leadership Style is giving not-significant contribution on State Civilians Official’s performance of The Islamic State University of Raden Fatah Palembang Regency; 2) Motivation is significantly affects State Civilians Official’s performance of The Islamic State University of Raden Fatah Palembang Regency; 3) Work Discipline is significantly affects State Civilians Official’s performance of The Islamic State University of Raden Fatah Palembang Regency; 4) All independent variables affect on State Civilians Official’s performance of The Islamic State University of Raden Fatah Palembang Regency. Abstract Penelitian ini bertujuan : 1) Untuk mengetahui apakah Gaya Kepemimpinan berpengaruh terhadap Kinerja Pegawai Aparatur Sipil Negara pada Univeritas Islam Negeri Raden Fatah Palembang; 2) Untuk mengetahui apakah Motivasi berpengaruh terhadap Kinerja Pegawai Aparatur Sipil Negara pada Univeritas Islam Negeri Raden Fatah Palembang; 3) Untuk mengetahui apakah Disiplin Kerja berpengaruh terhadap Kinerja Pegawai Aparatur Sipil Negara pada Univeritas Islam Negeri Raden Fatah Palembang; 4) Untuk mengetahui apakah secara bersama-sama Gaya Kepemimpinan, Motivasi dan Disiplin Kerja berpengaruh terhadap kinerja Pegawai Aparatur Sipil Negara. Populasi dalam penelitian adalah Pegawai Aparatur Sipil Negara pada Universitas Islam Negeri Raden Fatah Palembang yang berjumlah 152 orang pegawai. Sampel dalam penelitian berjumlah 110 orang sebagai responden. Alat analisis menggunakan Analisis Regresi Linear Berganda, Uji t, Uji F, dana Analisis Koefisien Determinasi. Kesimpulan : 1) Gaya Kepemimpinan tidak berpengaruh terhadap kinerja Pegawai Aparatur Sipil Negara Universitas Islam Negeri Raden Fatah Palembang; 2) Motivasi secara signifikan mempengaruh tingkat kinerja Pegawai Aparatur Sipil Negara Universitas Islam Negeri Raden Fatah Palembang; 3) Disiplin Kerja secara signifikan mempengaruh tingkat kinerja Pegawai Aparatur Sipil Negara Universitas Islam Negeri Raden Fatah Palembang; 4) Semua Variabel bebas berpengaruh terhadap kinerja Pegawai Aparatur Sipil Negara pada Universitas Islam Negeri Raden Fatah Palembang.